Transarterial Chemoembolization Combined With Hepatectomy for the Treatment of Intermediate-Stage Hepatocellular Carcinoma - Zhou, Qunfang; Tuo, Fei; Li, Ruixia; Wang, Xiaohui; Wang, Juncheng; Huang, Zhimei; Chen, Minshan; Huang, Jinhua (Frontiers in Oncology, 2020)
Background Transarterial chemoembolization (TACE) is currently the recommended treatment for intermediate-stage hepatocellular carcinoma (HCC). Liver resection (LR) may be an effective option, although recurrences are not uncommon. TACE prior to LR has been proposed as an even better alternative. Methods Patients with intermediate-stage HCC who underwent curative resection were enrolled between January 2007 and December 2015. We compared overall survival (OS) and recurrence-free survival (RFS) for the 2 groups using the Kaplan-Meier method, and we determined independent risk factors for death and recurrence using multivariate regression analyses. Results A total of 488 patients with HCC at BCLC B (265 patients with LR, 223 patients with TACE+LR) enrolled from our center. Mean follow-up was 40.2 (range, 3.0–128.7) months. For patients receiving TACE+LR and LR, estimated 1-, 3-, and 5-year OS rates were 90.6% and 73.3%, 61.7% and 43.5%, and 52.9% and 33.8%, respectively (all P < 0.001) and estimated 1-, 2-, and 3-year RFS rates were 54.6% and 39.4%, 41.4% and 29.4%, and 36.3% and 26.3%, respectively (P < 0.001, P = 0.002, and P = 0.008, respectively). Significant independent predictors of poor OS were more than 3 (vs. 3 or fewer) tumors (HR=2.19, 95% CI 1.69–2.84), non-anatomical (vs. anatomical) hepatectomy (HR=1.29, 95% CI 1.01–1.66), microscopic vascular invasion (HR=1.46, 95% CI 1.15–.90), cirrhosis (HR=2.41, 95%CI 1.88–3.01), and intraoperative blood transfusion (HR=1.29, 95% CI 1.01–1.66). Conclusion Preoperative TACE with LR may result in better oncological outcomes than either TACE or LR alone, without a substantial increase in morbidity, and could be considered an effective combination treatment for intermediate-stage HCC.